2001
DOI: 10.1080/028418501127346666
|View full text |Cite
|
Sign up to set email alerts
|

Abscesses of the breast: US-guided serial percutaneous aspiration and local antibiotic therapy after unsuccessful systemic antibiotic therapy

Abstract: US-guided aspiration with local antibiotic injection is a safe and effective approach to ABAs, cheaper than surgical drainage of these lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 17 publications
1
29
0
2
Order By: Relevance
“…According to recently published 2011 algorithm, a trial of ultrasound guided drainage is recommended for all fluid collections suggesting an abscess, regardless of size, which occur during the breastfeeding period, are caused by S. aureus, and lack a multiloculated structure. The greatest success is achieved with abscesses that are \3 cm in diameter [3,4]. Abscesses that are multiloculated or larger than 3 cm in diameter may fail ultrasound-guided drainage; thus, in such instances, early surgical evaluation for incision and drainage is strongly recommended [4].…”
Section: Discussionmentioning
confidence: 99%
“…According to recently published 2011 algorithm, a trial of ultrasound guided drainage is recommended for all fluid collections suggesting an abscess, regardless of size, which occur during the breastfeeding period, are caused by S. aureus, and lack a multiloculated structure. The greatest success is achieved with abscesses that are \3 cm in diameter [3,4]. Abscesses that are multiloculated or larger than 3 cm in diameter may fail ultrasound-guided drainage; thus, in such instances, early surgical evaluation for incision and drainage is strongly recommended [4].…”
Section: Discussionmentioning
confidence: 99%
“…As far as we know, Karstrup, et al [7] first reported the successful use of this technique in 1990, soon followed by other investigators. More recently, Imperiale, et al [2] resurrected the local instillation of antibiotics (40-160 mg of gentamicin) after sonographically-guided percutaneous aspiration in 26 patients with non-puerperal abscesses in whom systemic antibiotics failed, with only one failure requiring surgical drainage. Karstrup, et al.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound-guided drainage has been described in smaller series as a treatment for breast abscesses, the treatment for which has traditionally been surgery or even less frequently, punctures without imaging guidance [1][2][3][4]. In some institutions, the standard treatment still remains early incision under general anaesthesia combined with drainage tube insertion [5].…”
Section: Introductionmentioning
confidence: 99%
“…The standard management of lactational breast abscess used to be surgical incision and drainage, but recurrent aspiration has been recommended as a preferable alternative for many women1. This has been verified in studies both with2, 3 and without4, 5 the use of ultrasonographic guidance. The benefits of outpatient treatment are considerable for both the patient and the hospital.…”
Section: Introductionmentioning
confidence: 99%